Analisis Tata Ruang dalam Gedung Seni Pertunjukan Cak Durasim Surabaya - Ariqah Khaerunnisa Alindi; Muchlisiniyati Safeyah (Universitas Medan Area, 2026)
Surabaya was a city in Indonesia with increasingly developing regional arts. To showcase art performances, a facility was needed to accommodate such activities, namely a Performing Arts Building. Surabaya had a Performing Arts Building that served as a platform for artists to practice and present their works, located in the Cak Durasim building. However, the existing Performing Arts Building was still inadequate in terms of facilities and spatial layout. Therefore, this research aimed to identify the effectiveness of the spatial layout in supporting the building’s main function as a venue for performing arts and to provide design recommendations to make the performing arts building more functional and efficient, in accordance with the needs of its users—including artists, audiences, and administrators. This study employed a qualitative observation method, where the researcher closely observed the study site, recorded room sizes and spatial placements, and considered the relationships among aspects of the phenomenon by involving users, art enthusiasts, and spatial standards in the Cak Durasim Performing Arts Building in Surabaya. The research was expected to identify the effectiveness of the current spatial layout in supporting the building’s primary function and to offer design recommendations that would enhance its functionality and efficiency for all stakeholders involved.